2021
DOI: 10.3389/fmed.2021.737654
|View full text |Cite
|
Sign up to set email alerts
|

Urine Output Is Associated With In-hospital Mortality in Intensive Care Patients With Septic Shock: A Propensity Score Matching Analysis

Abstract: Background: The relationship between urine output (UO) and in-hospital mortality in intensive care patients with septic shock is currently inconclusive.Methods: The baseline data, UO, and in-hospital prognosis of intensive care patients with septic shock were retrieved from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. By drawing receiver operating characteristic (ROC) curves and comparing the areas under the ROC curves (AUC) to determine the predictive value of UO for in-hospital mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Patients who did not receive HSA or who received both 25% and 5% HSA within ICU admission were excluded. In the case of multiple admissions to the ICU, only the data from the first admission were extracted ( Chen et al, 2021 ; Hu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who did not receive HSA or who received both 25% and 5% HSA within ICU admission were excluded. In the case of multiple admissions to the ICU, only the data from the first admission were extracted ( Chen et al, 2021 ; Hu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…We extracted the data of the following variables from the MIMIC-IV (version 2.0) database on the first day of ICU admission: sex, age, weight, ethnicity, Simplified Acute Physiology Score II (SAPS II), SOFA score, Charlson Comorbidity Index, mean blood pressure (MBP), systolic blood pressure (SBP), diastolic blood pressure (DBP), respiratory rate, heart rate, pulse oximeter oxygen saturation (SPO 2 ), temperature, white blood cells (WBC) count, hemoglobin, platelet, blood urea nitrogen (BUN), serum creatinine (Scr), albumin, anion gap, bicarbonate, glucose, sodium, potassium, chloride, prothrombin time (PT), activated partial thrombin time (APTT), lactate, urine output, ventilator use, vasopressor use, renal replacement therapy (RRT) use, and comorbidities (atrial fibrillation, coronary artery disease [CAD], congestive heart failure [CHF], cerebrovascular disease, chronic lung disease, liver disease, diabetes mellitus, renal disease, and malignancy). The average values of laboratory parameters and vital signs within 24 h of ICU admission were used in this study ( Hu et al, 2021 ; Zhang et al, 2021 ; Wang et al, 2022 ). We extracted the data related to comorbidities using the International Classification of Diseases (ICD)-9 or ICD-10 diagnosis codes.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the overall 28-day mortality rate was lower in the usual care group of these more recent trials (20.6%) 61 compared to the intervention group of the original early goal-directed study (33.3%). 22 urine Output Oliguria is associated with worse outcomes in sepsis 62 and has long been a main trigger for fluid boluses. 63 However, urine output is influenced by neurohormonal regulation and kidney injury (e.g., acute tubular injury), and oliguria is a poor indicator of fluid responsiveness.…”
Section: Capillary Refill Time and Mottled Skinmentioning
confidence: 99%
“…Oliguria is associated with worse outcomes in sepsis 62 and has long been a main trigger for fluid boluses. 63 However, urine output is influenced by neurohormonal regulation and kidney injury ( e.g.…”
Section: Resuscitation Targetsmentioning
confidence: 99%
“…A retrospective study has demonstrated that UO is an independent risk factor for septic shock patients, and the decrease in UO is associated with a significant increase in in-hospital mortality. Meanwhile, the ability of using UO alone to predict in-hospital mortality of septic shock patients is comparable to the Sequential Organ Failure Assessment (SOFA) score [ 7 ]. Zhang et al found that UO on the admission of intensive care unit (ICU) is closely associated with in-hospital mortality in unselected critically ill patients, and is an independent predictor of in-hospital mortality independent of diuretic use [ 8 ].…”
Section: Introductionmentioning
confidence: 99%